Progress in Education of Electrical Measurements - Referowski, L.; Swisulski, D. (Elektronika ir Elektrotechnika, 2006)
In the paper the authors present the possibilities of preparing modern, educational tools which, in the form of virtual instruments, are very helpful for educational process concerning electrical measurements. These dynamic instruments make it possible to use during the lectures some demonstrations which better explain the presented theory of electrical measurements, especially when some kinds of phenomena are shown in a slow-down time scale. Another group of virtual instruments make it possible to simulate measuring sessions realized later in the university laboratory. The third group explains the idea of remote measurements with help of modern technologies. These measurements are realized on different industrial objects. The paper presents several solutions of educational virtual instruments designed by the team of Gdansk University of Technology using the software LabVIEW of National Instruments. Ill. 14, bibl. 15 (in English; summaries in English, Russian and Lithuanian).